A Novel m6A Gene Signature Associated With Regulatory Immune Function for Prognosis Prediction in Clear-Cell Renal Cell Carcinoma - Chen, Siteng; Zhang, Ning; Zhang, Encheng; Wang, Tao; Jiang, Liren; Wang, Xiang; Zheng, Junhua (Frontiers in Cell and Developmental Biology, 2021)
The important role of N6-methyladenosine (m6A) RNA methylation regulator in carcinogenesis and progression of clear cell renal cell carcinoma (ccRCC) is poorly understood by now. In this study, we performed comprehensive analyses of m6A RNA methylation regulators in 975 ccRCC samples and 332 adjacent normal tissues and identified ccRCC-related m6A regulators. Moreover, the m6A diagnostic score based on ccRCC-related m6A regulators could accurately distinguish ccRCC from normal tissue in the Meta-cohort, which was further validated in the independent GSE-cohort and TCGA-cohort, with area under the curve of 0.924, 0.867 and 0.795, respectively. Effective survival prediction of ccRCC by m6A risk score was also identified in the TCGA training cohort, and verified in the testing cohort and the independent GSE22541 cohort, with hazard ratio values of 3.474, 1.679 and 2.101 in the survival prognosis, respectively. The m6A risk score was identified as a risk factor of overall survival (OS) in ccRCC patients by the univariate cox regression analysis, which was further verified in both the training cohort and the independent validation cohort. The integrated nomogram combining m6A risk score and predictable clinicopathologic factors could accurately predict survival status of the ccRCC patients, with area under the curve values of 85.2%, 82.4% and 78.3% for the OS prediction in 1-, 3- and 5-year. Weighted gene co-expression network analysis (WGCNA) with functional enrichment analysis indicated that m6A RNA methylation might affect clinical prognosis through regulating immune functions in the patients with ccRCC.